Advances in Adhesive Systems and Universal Bonding Agents: A Review of Long-Term Clinical Outcomes and Failure Patterns (Bangladesh Journal of Medical Science, 2026)
Adhesive dentistry has progressed from multi-step etchand- rinse protocols to simplified self-etch and universal bonding agents designed to bond reliably to enamel, dentin, ceramics, metals and composite substrates. This narrative review evaluates advances in contemporary adhesive systems, with emphasis on long-term clinical outcomes, degradation mechanisms and patterns of failure observed in resin-based restorations. Evidence from clinical trials, systematic reviews and mechanistic laboratory studies indicates that universal adhesives have improved procedural flexibility and reduced technique complexity, but their long-term success remains highly dependent on substrate condition, moisture control, enamel pretreatment and chemical stability of the adhesive interface. Five-year randomized clinical data generally support acceptable retention of non-carious cervical lesion restorations restored with universal adhesives; however, several studies show superior marginal adaptation and lower discoloration when selective enamel etching or an etch-and-rinse strategy is used. Failures are rarely attributable to a single factor. Instead, they reflect progressive hydrolytic degradation of hydrophilic resin, collagen breakdown within the hybrid layer, incomplete monomer infiltration, polymerization stress, occlusal loading, caries risk and operator-related variables. The 10-methacryloyloxydecyl dihydrogen phosphate monomer has strengthened chemical interaction with hydroxyapatite and zirconia, but this advantage can be compromised by water sorption, acidic monomer incompatibility and suboptimal application. Current evidence favors selective enamel etching, active adhesive application, adequate solvent evaporation and careful case selection. Future research should prioritize pragmatic longterm trials, standardized failure definitions, aging protocols that reflect oral conditions and development of bioactive, enzyme-inhibiting and less permeable adhesive interfaces.Bangladesh Journal of Medical Science Vol. 25. Supplementary Issue-2 (2026), Page : S192-S198